PELATIHAN PEMBUKUAN AKUNTANSI SECARA SEDERHANA DAN DIGITAL BAGI KELOMPOK UP2K-PKK DESA SEMBAWA KECAMATAN JALAKSANA - Dadang Suhendar; Dendi Purnama; Neni Nurhayati (LPPM Universitas Bina Bangsa, 2021)
The purpose of this community service activity is to increase knowledge and skills to the UP2K-PKK group of Sembawa village in carrying out simple and digital accounting bookkeeping. Metode the implementation of the activities used in this devotion using training methods. The number of participants who attended the devotional activities as many as 20 members of the UP2K-PKK group Sembawa Village. From the results of devotional activities that have been carried out that the participants enthusiastically participated in simple and digital accounting bookkeeping training. In theory, some participants understand the material that has been delivered by the speaker. But at the time of practice they are able to understand and practice simple accounting bookkeeping, grouping accounts, identifying and summing the balances of accounts in assets and assets. At the time of the practice of compiling income statements and financial statements, only a portion of participants were able to practice. In addition, during the practice of recording transactions into SME accounting applications some participants have difficulty in identifying and grouping the accounts used in each transaction. But after being given an understanding and accompanied by participants can record into SME accounting applications